The HN1/HMGB1 axis promotes the proliferation and metastasis of hepatocellular carcinoma and attenuates the chemosensitivity to oxaliplatin. (10th June 2022) - Wang, Ruhua; Fu, Yunong; Yao, Menglin; Cui, Xiaomeng; Zhao, Yan; Lu, Xinlan; Li, Yarui; Lin, Yiguang; He, Shuixiang
Abstract : Hematological and neurological expressed 1 (HN1) is closely associated with the proliferation and metastasis of various tumors. However, the physiological functions and clinical significance of HN1 in hepatocellular carcinoma (HCC) remain indistinct. In this study, we investigated the role of HN1 in the pathogenesis of HCC and the underlying mechanism using clinical data from HCC patients, in vitro experiments utilizing HCC cell lines and in vivo animal models. We demonstrated that the overexpressed HN1 in HCC was correlated with patients' adverse outcomes. The gain and loss of function experiments indicated that HN1 could promote the proliferation, migration, and invasion of HCC cells in vitro . Furthermore, we found that HN1 knockdown sensitized HCC cells to oxaliplatin. Mechanically, HN1 prevented HMGB1 protein from ubiquitination and degradation via the autophagy‐lysosome pathway, which was related to the interaction between HN1 protein and TRIM28 protein. In the nucleus, the downregulation of HMGB1 followed by HN1 knockdown resulted in increased DNA damage and cell death in the oxaliplatin‐treated HCC cells. In the cytoplasm, HN1 regulated autophagy via HMGB1. Furthermore, HN1 knockdown in combination with HMGB1 overexpression restored the aggressive phenotypes of HCC cells and the sensitivity of these cells to oxaliplatin. HN1 knockdown inhibited the tumor growth and metastasis, and promoted the anticancer efficiency of oxaliplatin in vivo . In conclusion, our data suggest that the HN1/HMGB1 axis plays an important role in the development/progression and chemotherapy of HCC. Our findings indicate that the HN1/HMGB1 axis may be a promising therapeutic target for HCC treatment. Abstract : Through in vitro and in vivo experiments and analysis of hepatocellular carcinoma (HCC) clinical sample/data, we found that HN1 played an important role in the development/progression and chemotherapy of HCC. The underlying mechanism identified found that HN1 prevented HMGB1 from ubiquitination and degradation via autophagy‐lysosome pathway. HMGB1 acted as the pivotal mediator of HN1 to promote HCC proliferation and metastasis. The HN1/HMGB1 axis may be a promising target for HCC treatment.